1998
DOI: 10.1038/sj.bmt.1701052
|View full text |Cite
|
Sign up to set email alerts
|

Autologous bone marrow transplantation for treatment of isolated central nervous system relapse of childhood acute lymphoblastic leukemia

Abstract: Summary:The purpose of this study was to assess the role of ABMT in children with ALL who are in 2nd CR after an early isolated CNS relapse. All children experiencing an isolated CNS relapse at 10 AIEOP centers (Associazione Italiana Emato-Oncologia Pediatrica) from 1986 to 1992 were eligible for this study. The series included 69 patients who relapsed within 3 years from diagnosis: 19 underwent ABMT, nine patients underwent ALLO-BMT from an HLA-identical sibling, and 41 received conventional chemotherapy (CHE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
26
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 13 publications
0
26
0
Order By: Relevance
“…Similar results with ABMT have been reported in another recent Italian Study which compared ABMT and chemotherapy in CNS relapses. 29 Although no definitive conclusions can be established from these experiences, extramedullary relapses appear to be treatable with ABMT.…”
Section: Discussionmentioning
confidence: 99%
“…Similar results with ABMT have been reported in another recent Italian Study which compared ABMT and chemotherapy in CNS relapses. 29 Although no definitive conclusions can be established from these experiences, extramedullary relapses appear to be treatable with ABMT.…”
Section: Discussionmentioning
confidence: 99%
“…[43][44][45][46] This study compares favorably with previous experiences using chemotherapy and historical unmanipulated autografting, reporting EFS ranging from 33 to 56% for CNS relapses, 69% for any extramedullary relapse and from 41 to 61% for late relapses. [12][13][14][15][16][17][18][19][20][21][22][23][24][25] In a previous matched-pair analysis for late medullary relapses, autologous transplantation, reporting an EFS of 41%, was of no benefit, compared with chemotherapy. 20 Patient selection may differ, as T-lineage ALL was excluded from this B-lineage ALL study.…”
Section: Discussionmentioning
confidence: 99%
“…[10][11][12][13][14] Autologous transplantation may be an alternative to chemotherapy for ALL in CR2 after low-risk relapse. [15][16][17][18][19][20][21][22][23][24][25] In 2001, we reported a study that showed the feasibility and efficacy of an innovative protocol for autologous transplantation of purified peripheral hematopoietic stem cells in 12 pediatric patients with pediatric B-cell-precursor ALL after isolated extramedullary and/or late relapse. 26 This strategy aimed to ensure the best available treatment for low-risk relapsed ALL children and to avoid the toxicity of allogeneic transplantation.…”
Section: Introductionmentioning
confidence: 99%
“…20 It was suggested that ABMT represents a valuable therapeutic option for patients with no matched sibling in second remission after an isolated CNS relapse. 21 Different conditioning regimens have been used prior to BMT in an attempt to reduce leukaemic relapse without increasing toxicity from BMT. 11 Melphalan and TBI have been used in this institution as a conditioning regimen for more than a decade instead of the more commonly used regimen of cyclophosphamide and TBI.…”
Section: Bone Marrow Transplantationmentioning
confidence: 99%